Spark of the everflame: the kindred's curse saga. Book one - Cole, Penn (Cole, Penn. Kindred's curse saga, 2023)
When old secrets catch fire, everything will burn. In a mortal world colonized by the gods and ruled over by the Descended, their cruel offspring, Diem Bellator yearns to escape the insular life of her poor village. Her mother's sudden disappearance--and the discovery of a dangerous secret about her past--offer Diem an unexpected opportunity to enter the dark world of Descended royalty and unlock the web of mysteries her mother left behind. With the dying King's handsome, mysterious heir watching her every move, and a ruthless mortal alliance recruiting her to join the growing civil war, Diem will have to navigate the unwritten rules of love, power, and politics in order to save her family--and all of mortalkind.